PHYSIOLOGICAL STATUS AND FEEDING MANAGEMENT OF LOCAL AND IMPORTED HORSES AT ROYAL SPORTHORSE BALI - N. M, Aushaf; Putra, I G. A. A.; Puspani, E. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
The aim of this research was to investigate the physiological status and feeding management of local and imported horse groups reared at Royal Sporthorse Bali. Observation was conducted for three months, started from early February until the end of April in 2019. Data were obtained through field observation, and analysis of feed samples in the Laboratory of Nutrition and Forage Science of Udayana University. Data processing was performed using independent sample T Test. Result showed that respiratory rate of local horses was (P<0.05) lower than of imported horses, both at day and night times. The respiration rates of local horses were 28 times per minute and 32 times per minute, while of the imported horses were 39 times per minute and 44 times per minute for day and night times, respectively. The pulse rate and body temperature of imported horses (P>0.05) tended to be higher but were not significant differences. Grass consumption per metabolic weight of imported horses 0.22 kg was (P<0.01) significantly lower than 0.28 kg of local horses. However, the concentrate consumption per metabolic weight of imported horses 0.09 kg was (P<0.01) significantly higher than 0.05 kg of local horses. Crude protein of daily feed fed to the horses at the Royal Sporthorse Bali was (P<0.01)significantly higher compared to the National Research Council recommended in 2007. Key words: physiological status, respiration rate, pulse rate, temperature, nutrition.